Jugular foramen syndrome caused by choleastatoma - Erol, FS; Kaplan, M; Kavakli, A; Ozveren, MF (Elsevier, 2005)
Unilateral paresis of 9th-11th cranial nerves together is defined as jugular foramen (Vernet's) syndrome, A cholesteatoma case that penetrated into intracranial area after eroding temporal bone and led to jugular foramen syndrome is presented here, since such a case has not been reported in the literature hitherto. A 46-year-old male patient was evaluated for hoarseness. It was learnt from his anamnesis that he had been operated for otitis media nearly 20 years ago. Uvula deviated towards right. Loss of gag reflex was remarkable on the left. Paresis was found on the left vocal cord. There was weakness in rotation of the head to the right, Computerized tomography (CT) scan revealed that the temporal bone lost its integrity and that there was an extra-axial hypodense mass neighboring pontocerebellum. Post-contrast magnetic resonance imaging showed that the mass, which showed thin. regular circular contrasting and which was hypointense in T1-weighted MR and hyperintense in T2-weighted MR. extended to the left jugular foramen. The mass was totally removed with left sub-occipital approach in the treatment. After the treatment, hoarseness, weakness in the rotation movement of the head and loss of gag reflex recovered totally, while deviation in the uvula was permanent. Cholesteatomas can extend to posterior fossa and cause jugular foramen syndrome, Early surgery is important to completely reverse the lost nerve functions in treatment. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: cholesteatoma; jugular foramen syndromes; Vernet's syndrome